“Orgy of Blood” vs “Getting Food on the Table”: Negotiating Essentializing Discourses around the Faroese Grindadráp - Caputo-Nimbark, Roshni (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
The Faroese grindadráp is a centuries-old, dramatic spectacle in which an entire pod of pilot whales is slaughtered en masse in a blood-soaked harbour, followed by the distribution of whale meat and blubber to participating villagers. For many Faroese, grindadráp is an embodiment of nationalism, achieved through the primordialization of tradition and the securitization of a beloved food source. For many outsiders, particularly since aggressive anti-whaling campaigns have besmirched the Faroese reputation in the international gaze, grindadráp amounts to a barbarous anachronism intolerable in modern society. This study takes a multivocal digital ethnographic approach to explore how politics, economics, and ethics of grindadráp are understood through social media debates, institutional rhetoric, and an interview. It considers how essentializing discourses of tradition and modernity are framed, their implications for collective action, and some potentialities that are revealed through a shift in perspective from barbaric ritual to dynamic economic practice.